Protective Effect of Thioctic Acid on Renal Ischemia–reperfusion Injury in Rat - Ahmadvand, Hassan (Int J Prev Med, 2019)
BACKGROUND: We investigated the effect of thioctic acid (TA) on kidney function, oxidative stress, and inflammatory status in serum and kidney homogenates of a rat subjected to ischemia–reperfusion injury (IRI). MATERIALS AND METHODS: Thirty male Wistar rats were randomly divided into three equal groups: sham, IR, and IR + TA in 50 mg/kg once-daily intraperitoneal injection for 2 weeks, before IR induction. The levels of urea and creatinine (Cr) in the serum of rats were measured. Malondialdehyde and nitric oxide (NO) as stress oxidative markers; tumor necrosis factor-α, interleukin-6, and myeloperoxidase as inflammatory markers, as well as activities of superoxide dismutase, glutathione peroxidase and catalase, and glutathione (GSH) level in both serum and kidney homogenates were determined. RESULTS: Cr and urea increased in serum of IR group. Furthermore, levels of oxidative stress and inflammatory markers in serum and kidney homogenates of the cited group were higher than the sham group. TA not only decreased the levels of Cr, urea, oxidative stress, and inflammation but also elevated the level of GSH and activities of antioxidant enzymes (P < 0.001). CONCLUSIONS: The findings showed that TA protected IR rat against kidney dysfunction and IRI due to reinforcing endogenous antioxidant and subtracting of inflammatory markers.